EMPLOYEE MANAGEMENT EFFORTS TO IMPROVE ASN DISCIPLINE AND COMPETENCE IN THE DEPARTMENT OF EDUCATION AND CULTURE OF CENTRAL PAPUA PROVINCE - Alesina Yogi; Petrus P. Roreng; Agustinus Ba’ka (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the human resource management strategies in improving the discipline and competence of civil servants (ASN) at the Department of Education and Culture of Central Papua Province. The research employed a qualitative descriptive approach with data collected through observations, in-depth interviews, and document analysis. Six key informants were selected purposively, representing structural officials and operational staff, providing a comprehensive perspective on the actual conditions of personnel management within the organization. The findings reveal that the discipline level of civil servants is considered moderate but not yet optimal. Approximately 55–60% of ASN comply with working hours and task completion targets, while the rest face challenges related to work culture adaptation and weak internal supervision. Competence levels also vary; Recruited civil servants adapt more quickly to digital technologies, while many senior staff still require assistance in operating administrative applications such as MyASN, SIPD, and e-Kinerja. Differences in educational background, work experience, and organizational habits among districts contribute to gaps in both discipline and competency levels . The main obstacles include low intrinsic motivation, inconsistent supervision, limited technology utilization, and low participation in training programs. Moreover, diverse working cultures and habits among employees hinder the standardization of professionalism and service quality within the department. To address these issues, the department has designed several strategic approaches, including: 1) Enhancing digital-based supervision by integrating online attendance with performance assessments; 2) Implementing a consistent and fair reward-and-punishment system to strengthen accountability; 3) Improving ASN competence through technical workshops, peer mentoring, and the adoption of e-learning methods to overcome budget limitations; 4) Applying a local wisdom-based approach by fostering a family-oriented and deliberative work environment to improve cultural integration and employee motivation. The study concludes that effective personnel management strategies should emphasize structured employee development, technological adaptation, and consistent performance-based evaluation. These efforts are expected to improve organizational performance and enhance the quality of public services, particularly in the education and cultural sectors of Central Papua Province.